(untitled) (Ameghiniana, 2013)
The carboníferous cnidaría Cladochonus harringtoni nov. sp. is described and figured. The new species comes from Barreal and belongs to the Leoipustula Zone, Hoyada Verde Forrnatíon. Its relationships with C. tenuicollis M’Coy, C. crassus (M’Coy ) and C. amosi Sabattini y Noirat are discussed.